2020
DOI: 10.3889/oamjms.2020.5167
|View full text |Cite
|
Sign up to set email alerts
|

Management of Mucopolysaccharidosis Type I in Saudi Arabia: Insights from Saudi Arabia

Abstract: Mucopolysaccharidosis (MPS) is a group of rare disorders that are characterized by intracellular accumulation of glycosaminoglycans with subsequent cellular and organ dysfunction. In the Middle East, especially Saudi Arabia, higher prevalence of MPS type I was observed compared to reported rates from European countries and the United States (U.S). The present work was developed as a part of the Saudi MPS Group’s efforts to address the current situation of MPS type I in Saudi Arabia and to reach a national cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Although the current observation lacked electron microscopic observations of the GAG membrane deposition, radiographic findings, along with IDUA deficiency, proved beyond a doubt that MPS I was the underlying disease in the patient. Another study reported a similar neonatal manifestation as described in this case, except the patient was diagnosed with MPS II [ 9 ]. However, it should be noted that MPS II is diagnosed histologically with pulmonary interstitial glycogenosis correlating with classical MPS II clinical manifestations [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Although the current observation lacked electron microscopic observations of the GAG membrane deposition, radiographic findings, along with IDUA deficiency, proved beyond a doubt that MPS I was the underlying disease in the patient. Another study reported a similar neonatal manifestation as described in this case, except the patient was diagnosed with MPS II [ 9 ]. However, it should be noted that MPS II is diagnosed histologically with pulmonary interstitial glycogenosis correlating with classical MPS II clinical manifestations [ 9 , 10 ].…”
Section: Discussionsupporting
confidence: 71%
“…However, MPS I with interstitial lung disease as a primary presenting manifestation has not been extensively reported on [ 13 , 15 ]. In the current case, MPS I was diagnosed with the neonate showing interstitial lung disease, which is an uncommon feature of MPS I [ 2 , 9 , 10 , 11 , 22 , 23 , 24 ]. The official clinical guidelines of the American Thoracic Society (ATS) for evaluating childhood interstitial and diffuse lung disease (chILD) state that specialized consultations should be considered after excluding the common causes of diffuse lung diseases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations